Federal Republic of Nigeria approved budget : 2000 fiscal year - Federal Republic of Nigeria (Abuja : Budget office of the Federal Ministry of Finance, 1999)
This book is the 2000 fiscal year approved budget of the federal government of Nigeria
Volume 1: 2000 fiscal year
osa; 04/07/18
Arch
Keywords: Budget; Nigeria